A prospective study of acute cerebrovascular disease in the community: the Oxfordshire Community Stroke Project 1981-86. 1. Methodology, demography and incident cases of first-ever stroke. Issue 11 (November 1988) - Bamford, J; Sandercock, P; Dennis, M; Warlow, C; Jones, L; McPherson, K; Vessey, M; Fowler, G; Molyneux, A; Hughes, T
Abstract : A prospective study of acute cerebrovascular disease in a community of about 105, 000 people is reported. The study protocol combined rapid clinical assessment of patients with accurate diagnosis of the pathological type of stroke by CT or necropsy, whether or not they were admitted to hospital. The study population was defined as those people who were registered with one of 50 collaborating general practitioners (GPs). Referrals to the study were primarily from the GPs though, to ensure complete case ascertainment, hospital casualty and admission registers, death certificates and special data from the Oxford Record Linkage Study were also scrutinized. Six hundred and seventy five cases of clinically definite first-ever in a lifetime stroke were registered in four years yielding a crude annual incidence of 1.60/1, 000 or 2.00/1, 000 when adjusted to the 1981 population of England and Wales. The age and sex specific incidence rates for first stroke showed a steep rise with age for both sexes. The odds of a male sustaining a first stroke were 26% greater than those of a female. Ninety one per cent of patients were examined in a median time of four days after the event by a study neurologist and 88% had cerebral CT or necropsy.